Critical illness polyneuropathy, myopathy and neuronal biomarkers in COVID-19 patients: A prospective study. Issue 7 (July 2021) - Frithiof, Robert; Rostami, Elham; Kumlien, Eva; Virhammar, Johan; Fällmar, David; Hultström, Michael; Lipcsey, Miklós; Ashton, Nicholas; Blennow, Kaj; Zetterberg, Henrik; Punga, Anna Rostedt
Highlights: Critically illness polyneuropathy/myopathy (CIN/CIM) was more prevalent in COVID-19 ICU patients with severe illness. Neurofilament light chain (NfL) and glial fibrillary acidic protein (GFAp) levels were higher in the CIN/CIM group and GFAp correlated with motor nerve amplitudes. COVID-19 patients who later developed CIN/CIM had significantly higher NfL and GFAp in the early phase of ICU care. Abstract: Objective: The aim was to characterize the electrophysiological features and plasma biomarkers of critical illness polyneuropathy (CIN) and myopathy (CIM) in coronavirus disease 2019 (COVID-19) patients with intensive care unit acquired weakness (ICUAW). Methods: An observational ICU cohort study including adult patients admitted to the ICU at Uppsala University Hospital, Uppsala, Sweden, from March 13th to June 8th 2020. We compared the clinical, electrophysiological and plasma biomarker data between COVID-19 patients who developed CIN/CIM and those who did not. Electrophysiological characteristics were also compared between COVID-19 and non-COVID-19 ICU patients. Results: 111 COVID-19 patients were included, 11 of whom developed CIN/CIM. Patients with CIN/CIM had more severe illness; longer ICU stay, more thromboembolic events and were more frequently treated with invasive ventilation for longer than 2 weeks. In particular CIN was more frequent among COVID-19 patients with ICUAW (50%) compared with a non-COVID-19 cohort (0%, p = 0.008). Neurofilament light chain (NfL) and glial fibrillary acidic protein (GFAp) levels were higher in the CIN/CIM group compared with those that did not develop CIN/CIM (both p = 0.001) and correlated with nerve amplitudes. Conclusions: CIN/CIM was more prevalent among COVID-19 ICU patients with severe illness. Significance: COVID-19 patients who later developed CIN/CIM had significantly higher NfL and GFAp in the early phase of ICU care, suggesting their potential as predictive biomarkers for CIN/CIM.